qanda-logo
search-icon
Símbolos
Problema
solution-image
$6$ Elimina los signos de agrupación y halla el resultado : $a\right)$ $6x^{4}$ $-\left(3x^{4}-2x+1\right)=$ $2\right)$ $2x^{3}-\left(-4x-2x^{3}\right)=$ $c\right)$ $7x^{4}-\left(6x-5-2x^{4}\right)=$ $d\right)$ $8x^{3}-3x^{4}+1+\left(2x^{2}+3x^{2}+5\right)=$ $e\right)$ $5x^{3}-\left(2x^{3}-4\right)+\left(3x^{2}+6\right)=$ ) $3x^{4}-\left(-3x^{4}+6x^{2}+x-\left(2x^{4}+3\right)\right)=$ $9$ $8x^{4}$ $+|-5x^{4}$ $-\left(2x^{4}-3x+4\right)\right)$ $=$ -
Secundaria
Aritmética y álgebra
Búsquedas: 124
Solución
answer-user-profile-image
Profesor de Qanda - Giordani9
answer-reply-image
answer-reply-image